Język w czasach globalizacji - Białek, Ewa (Acta Neophilologica, 2023)
The article focuses on the relationship between globalization and language in the modern world. In the theoretical part of the paper the author explains the concepts of globalization and westernization before discussing the definition of the lexeme globalization in English, Polish and Russian. In the practical part, such words as mall, strip mall, food hall, food mall, food court, droguerie, discount store are analyzed. Assimilation processes and the registration of new lexis in dictionary sources (are used to) demonstrate the mechanism of the impact of progressing globalization processes on the language – the gradual transition from foreign realities and an unknown word to the assimilation of these realities together with the names. The dynamic changes in the language system are caused by the dynamic changes that the modern world is undergoing. The analysis is conducted on material from English, Polish, Russian and – partly – Ukrainian.